Handling the "difficult" biopsy specimen - JB Thapa (Association of Clinical Pathologists of Nepal, 2014)
No abstract available. DOI: http://dx.doi.org/10.3126/jpn.v4i7.10323   Journal of Pathology of Nepal (2014) Vol. 4, I